Peran Pemerintah Dan Masyarakat Dalam Pengelolaan Program Pendidikan Kecakapan Hidup - Nugraha, Muhamad Aditia; Amanda, Virna Tria; Zidane, Rizky Akhmad; Karwati, Lilis (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
This study examines the important roles of the government and society in managing life skills education programs in Indonesia. The objective of the research is to understand the collaboration between both parties in enhancing the effectiveness of these programs. The method employed is a literature study approach, collecting and analyzing various sources of information. The findings indicate that government support in terms of policies, funding and resources, oversight, and evaluation is crucial, while the role of society in participation and cooperation enhances relevance and sustainability. These findings suggest that the synergy between the government and society is key to achieving sustainable and effective life skills education objectives. This study recommends improving communication and collaboration between both parties to optimize program outcomes.